Investing in agricultural water management to benefit smallholder farmers in Zambia. AgWater Solutions Project country synthesis report. - Evans, Alexandra E.V.; Giordano, Meredith A.; Clayton, Terry (International Water Management Institute, 2012)
This Working Paper summarizes research conducted as part of the AgWater Solutions Project in Zambia from 2009 to 2012. Approximately 48 million hectares (Mha) of land in Zambia are suitable for agricultural use. An estimated 67% of the Zambian labor force is employed in the agriculture sector. Researchers from the AgWater Solutions Project examined ways of improving the motor pump supply chain, how to make better use of small reservoirs and improving the function of horticultural markets. Researchers also explored gendered aspects of agricultural systems. Research methodologies included rapid rural appraisals, interviews, survey questionnaires and literature reviews. Research suggests that small improvements in the motor pump supply chain could catalyze significant increases in farm productivity similar to what has been achieved in parts of Asia. Measures likely to improve the performance of small reservoirs include coordinating and integrating multiple users, facilitating multiple institutional arrangements and strengthening existing policies, procedures and links within organizations along with more transparency in planning, contract awards and construction. Out-grower schemes can be improved by building trust, market information for smallholder farmers and reducing transaction costs for companies. Improving horticultural markets will depend on developing a legal framework in which all major stakeholders participate as stipulated under the Bus Stations and Markets Act and/or Public Private Partnership Act of Zambia.